Discovery of Plasmodium (M)TRAP-aldolase interaction stabilizers interfering with sporozoite motility and invasion - Boucher, Lauren E.; Muthinja, Mendi; Frischknecht, Friedrich (ACS infectious diseases, 2018)
As obligate, intracellular parasites, Plasmodium spp. rely on invasion of host cells in order to replicate and continue their life cycle. The parasite needs to traverse the dermis and endothelium of blood vessels, invade hepatocytes and red blood cells, traverse the mosquito midgut, and enter the salivary glands to continue the cycle of infection and transmission. To traverse and invade cells, the parasite employs an actomyosin motor at the core of a larger invasion machinery complex known as the glideosome. The complex is comprised of multiple protein–protein interactions linking the motor to the internal cytoskeletal network of the parasite and to the extracellular adhesins, which directly contact the host tissue or cell surface. One key interaction is between the cytoplasmic tails of the thrombospondin related anonymous protein (TRAP) and aldolase, a bridging protein to the motor. Here, we present results from screening the Medicines for Malaria Venture (MMV) library of 400 compounds against this key protein–protein interaction. Using a surface plasmon resonance screen, we have identified several compounds that modulate the dynamics of the interaction between TRAP and aldolase. These compounds have been validated in vitro by studying their effects on sporozoite gliding motility and hepatocyte invasion. One of the MMV compounds identified reduced invasion levels by 89% at the lowest concentration tested (16 μM) and severely inhibited gliding at even lower concentrations (5 μM). By targeting protein–protein interactions, we investigated an under-explored area of parasite biology and general drug development, to identify potential antimalarial lead compounds.
Gesehen am 07.05.2019